Nanosilica Coatings to Improve the Tensile Bond Strength of Cementitious Grouts. Issue 10 (October 2019) - De la Varga, Igor; Muñoz, José F.; Spragg, Robert P.; Nickel, Caleb A.; Bohn, Lucas; Fay, Ariana; Graybeal, Benjamin A.
The use of prefabricated bridge elements (PBEs) is becoming more common as bridge owners strive to construct robust bridges with minimal impacts on the traveling public. Concrete PBEs offer advantages with regards to quality and construction safety; however, to perform adequately, the installed structural system must include strong, durable connections between the components. Typically, field-cast cementitious grouts are used to connect the PBE. This type of material has at times shown serviceability problems associated to dimensional instability, primarily in the form of shrinkage cracking. A direct consequence is the potential bond degradation between the grout connections and the concrete PBE. This study investigated the use of colloidal nanosilica suspensions as a surface preparation technique to increase the bond strength between the precast components and the field-cast grout. Experimental results, including pull-off bond data and a careful microstructural analysis, strongly suggest that nanosilica coatings interact at the concrete–grout interface to increase the bond strength. A simple initial cost analysis is also discussed.